Growth stage-specific responses of cucumber to salinity stress: germination, seedling establishment, and vegetative development - Shaik, Azeezahmed; Karthikeyan, Raghupathy; Kousik, Chandrasekar S. (Frontiers in Plant Science, 2025)
Salinity is a major abiotic stress limiting cucumber (Cucumis sativus L.) production, especially in areas where saltwater intrusion is present and brackish water is used for irrigation. This study evaluated salinity tolerance in cucumber cultivars across three growth stages—germination, seedling, and vegetative—using various concentrations of brackish water ranging from 0 to 31 dS·m-1. Germination results revealed distinct cultivar responses, with ‘Diva’ performing well and ‘Striped Armenian’ showing poor emergence. However, at the seedling and vegetative stages, ‘Striped Armenian’ consistently outperformed others under salinity stress, maintaining higher survival, shoot growth, and stress tolerance indices. In contrast, cultivars such as ‘Diva’ and ‘H-19 Little Leaf’ were more sensitive at later stages despite good early germination. Brackish water concentrations above 6 dS·m-1 led to significant reductions in biomass and shoot traits, with complete seedling mortality observed at 22 dS·m-1. At the vegetative stage, increasing salinity resulted in reduced shoot length, dry weight, and gas exchange parameters, including stomatal conductance, transpiration, photosynthesis, and intercellular carbon dioxide concentration. While intrinsic water use efficiency increased under severe stress, it did not consistently indicate overall tolerance. The contrasting performance of cultivars across stages underscores the complexity of salinity responses. Cultivar ‘Striped Armenian’ consistent resilience suggests its potential for use in areas where saltwater intrusion is a problem. These findings emphasize the importance of stage-specific screening and the integration of physiological traits to accurately identify salt-tolerant cultivars. This approach provides a reliable strategy for improving cucumber productivity under saline conditions and supports breeding efforts targeting stress-resilient varieties.